Masa Kerja sebagai Faktor Risiko Gangguan Fungsi Paru pada Pekerja yang Terpapar PM10: Tinjauan Literatur - Fitri Maharani; Winda Trijayanthi Utama; M. Yogie Fadli; Sutarto Sutarto (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Occupational exposure to particulate matter (PM₁₀) represents a significant health risk. Although the association between PM₁₀ exposure levels and impaired lung function has been well demonstrated in numerous studies, epidemiological literature shows highly contradictory findings regarding the relationship between exposure duration, commonly measured as “Length of Service” and lung function. To explore the sources of this inconsistency, this review examined literature published between 2020 and 2025 using a narrative synthesis approach. The analysis revealed that the divergent findings are not driven by biological factors, but rather by systematic methodological limitations. Non-significant results in several studies can be attributed to three major weaknesses: (1) Length of Service is a weak proxy variable that fails to capture the crucial intensity (dose) of exposure; (2) substantial statistical multicollinearity between Length of Service and Age, which distorts the estimated associations; and (3) the Healthy Worker Effect (HWE), a selection bias that is almost inevitable in occupational epidemiology studies especially those using cross-sectional designs, which systematically attenuates true associations. Therefore, non-significant findings related to Length of Service should not be interpreted as evidence of the absence of harm from chronic exposure. The relationship likely exists but is “masked” by design biases and the limitations of a weak proxy. Future research should avoid relying on Length of Service as a sole exposure indicator and instead adopt cumulative exposure metrics that are more representative.